Strictureplasties performed by laparoscopic approach for complicated Crohn's disease. A prospective, observational, cohort study. Issue 10 (October 2021) - Sampietro, Gianluca M; Colombo, Francesco; Frontali, Alice; Baldi, Caterina; Conti, Lorenzo; Dilillo, Dario; Penagini, Francesca; Nebuloni, Manuela; D'Addio, Francesca; Fiorina, Paolo; Maconi, Giovanni; Corsi, Fabio; et al.
Abstract: Background: Laparoscopy is considered the best surgical approach for Crohn's Disease (CD), and strictureplasty a reliable alternative to intestinal resection. Nevertheless, their association has never been evaluated. Aim: To investigate feasibility and safety of conventional (SP) and non-conventional (NCSP) strictureplasties, using laparoscopy, for complicated CD. Methods: Starting January 2008, a prospective cohort study was performed, in consecutive, unselected patients, undergoing primary surgery for CD (Group-A). The residential database (CD-CARD) was used for the retrospective extraction of control patients (Group-B). Univariate and multi-variate analysis of pre-operative characteristics, intra-operative findings, morbidity, and intra-abdominal septic complications (IASCs) was performed. Results: Between January 2008 and December 2019, 331 patients received 162 SPs, 138 NCSPs, and 373 resections (Group-A). From the CD-CARD, 227 control patients received 159 SPs, 117 NCSPs, and 271 resections (Group-B) (ns). Preoperatively, Group-A presented batter nutritional status and received more biological therapies, Group-B more steroids. Group-A presented less abdominal abscesses, planned ostomies, minor complications, shorter operating time and hospitalization than Group-B, but similar major complications, IASCs and anastomotic leaks. IASCs were related to older age, elevated inflammatory indices, and preoperative treatment with high-risk drugs. Conclusions: SP and NCSP are feasible by laparoscopy, with low morbidity rate, confirming the advantages of both minimally invasive and conservative surgery.